(untitled) (KONFERENSIYA, 2026)
This article examines the cognitive processes involved in note-taking during consecutive interpreting. It explores how interpreters use attention, short-term memory, information processing, and analytical thinking to create effective notes that support accurate and coherent translation. The article discusses key principles of interpreter note-taking, including symbols, abbreviations, structuring, and logical sequencing. It also highlights how note-taking enhances cognitive load management, improves message retention, and contributes to higher translation quality.